Lovastatin differentially regulates α7 and α4 neuronal nicotinic acetylcholine receptor levels in rat hippocampal neurons - Borroni, María Virginia (2020)
Fil: Borroni, María Virginia. Universidad de Buenos Aires. Facultad de Arquitectura, Diseño y Urbanismo. Instituto de Tecnología en Polímeros y Nanotecnología; Argentina